The Italian national character seen from the outside and from within - Viljanen-Belkasseh Paula (PAZMANY PETER CATHOLIC UNIV, FACULTY HUMANITES, 2025)
This paper studies the auto-images of Italians in the second half of the 19th century and compares them with the images of the Italian national character presented by Finnish travellers in their travelogues of the same period. The approach of the analysis is imagological, that is, images regarding Italians as the ‘self’ and as the ‘Other’ are examined through a study of their literary representations. In these representations, stereotypes are often present – being closely connected to the notion of national character – and influential as they affect the image formation process. This study aims to analyse how Italians’ auto-images, often auto-stereotypes, relate to the images of Italians reported in the Finnish travelogues.